Clinico-demographical Profile of Pelvis and Acetabular Fracture Presenting in Tertiary Care Center of Nepal: An Observational Study - Ranjib Jha; Santosh Thapa; Asish Rajthala (Journal of Nepal Medical Association)
Introduction: Pelvis and acetabular fractures are complex, high-energy trauma and are often associated with life threatening injuries. The majority of them require surgical intervention and extensive rehabilitation. The epidemic figures are necessary to make plan for their management and its complications. We aim to analyze epidemiological profile of patients presented with pelvis and acetabular fracture in our center. Methods: This was observational cross-section study, analyzed on patients admitted with pelvis and acetabular fracture at a tertiary care center through emergency and outpatient department between January to December 2023. The collected parameters were age, gender, mechanism of injury, site of injury, classification of fracture, associated other injuries, management operative or non-operative, early post-operative complications, duration of hospital stay, mortality and Intensive Care Unit admission and they were analyzed. Ethical approval was obtained from Institutinal Review Committee (Reference number: 19/2024) Results: There were 48 (7.27%) pelvis and/or acetabular fracture amongst 660 patient with traumatic fractures. Pelvic fracture was 29 (4.39%) and acetabular fracture was 16 (2.42%). The median age was 38 years (IQR: 25.25-46.75) and 36 (75%) were male. Thirty three (69%) patients required surgery, 17 (35%) patients had additional surgery for associated injury and 14 (29%) required intensive care unit admission. The median hospital stay was 12.5 days and mortality rate were 2%. Conclusions: The proportion of pelvis fracture was comparable to other studies while the proportion of actebular was comparatively higher in this study.